The pyrolysis of industrial alliaceous plant wastes: Illustration of process and characterization of products - Atila Caglar; Bahattin Aydinli (SAGE Publications, 2018)
Biomass is one of the renewable energy and material sources. Agricultural biomass wastes are in top list in terms of quantity and uniformity. The stalks, leafs, and peels of them have taken considerable attention for various purposes. The biomass and wastes in recycling of matter and recuperation of chemicals with thermochemical conversion techniques are an efficient way in environmental perspective. The alliaceous plant reaches huge amount and its peels take attention in terms of difficulty of recycling with potential valuable compounds like its pulp. Here the pyrolysis of this garlic peel wastes was accomplished to obtain various valuable solid and liquid products that were analyzed with miscellaneous methods (thermogravimetric analysis/differential thermal analysis, gas chromatography/mass spectrometry, and scanning electron microscope). Three basic zones were appeared in thermal analysis for pyrolysis process. The valorization of these wastes to obtain precious chemicals and combustible compounds equivalent to petroleum products was illustrated by this way. Also carbonaceous compounds have been sequestered in solid and liquid forms by this way. The main fuel additives, methanol was obtained in remarkable amount (22.5%) from the liquid products. Also, porous material was produced from the solid products.
Keywords: TK1001-1841; Production of electric energy or power. Powerplants. Central stations; TJ807-830; Renewable energy sources; 13. Climate action; 7. Clean energy; 12. Responsible consumption